2006
DOI: 10.1152/ajpheart.00220.2006
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical coronary microcirculatory constriction during ischemia: a synergic function for nitric oxide and endothelin

Abstract: . Paradoxical coronary microcirculatory constriction during ischemia: a synergic function for nitric oxide and endothelin. Am J Physiol Heart Circ Physiol 291: H1814 -H1821, 2006. First published April 28, 2006 doi:10.1152/ajpheart.00220.2006.-A paradoxical microcirculatory constriction has been observed in hearts of patients with ischemia, secondary to coronary stenosis. Here, using the isolated mouse heart (Langendorff), we examined the mechanism of this response, assuming involvement of nitric oxide (NO) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…The finding of increased basal microvascular resistance is in agreement with the documented hypo-perfusion of the remote viable region in patients with chronic myocardial infarction [51,52]. In previous ex-vivo experiments, we found a similar increase in coronary resistance in control hearts following L-NAME [30] suggesting impaired endothelial function and reduced NO bioavailability in the surviving myocardium. However, the mechanism(s) underlying the further increase in resistance during hypotension (paradoxical vasoconstriction) in the remote zone of infarcted heart remains to be elucidated, especially in relation to the observed significant increase of circulating ET-1 in MI as opposed to PGE 2 .…”
Section: Discussionsupporting
confidence: 89%
“…The finding of increased basal microvascular resistance is in agreement with the documented hypo-perfusion of the remote viable region in patients with chronic myocardial infarction [51,52]. In previous ex-vivo experiments, we found a similar increase in coronary resistance in control hearts following L-NAME [30] suggesting impaired endothelial function and reduced NO bioavailability in the surviving myocardium. However, the mechanism(s) underlying the further increase in resistance during hypotension (paradoxical vasoconstriction) in the remote zone of infarcted heart remains to be elucidated, especially in relation to the observed significant increase of circulating ET-1 in MI as opposed to PGE 2 .…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in spite of the documented ischemia, coronary microvascular tone increased, challenging the traditional view of maximal vasodilation during restricted flow and justifying the term "paradoxical vasoconstriction" to define such a phenomenon. This is the expression of an active increase in vascular tone as previously shown by the prompt reversal via papaverine or adenosine and by manipulation with eNOS inhibitors, endothelin blockade, and antioxidants (26).…”
Section: Discussionmentioning
confidence: 65%
“…Recently, both clinical and experimental studies (26,48) have demonstrated a "paradoxical" coronary microvascular constriction during severe reduction in perfusion pressure and myocardial ischemia. It is not known whether this may be a naturally occurring response to severe hypotension and ischemia, possibly intended to preserve capillary pressure, or whether it may be caused or enhanced by the presence of endothelial dysfunction, hence, aggravating myocardial ischemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from NHE1, a number of signaling molecules, such as protein kinase C (PKC), reactive oxygen species (ROS), NO, mitogen‐activated protein kinase (MAPK), phosphatidylinositol 3‐kinase (PI3K) are associated with ET‐1 16–20 . In particular, it is reported that ET‐1 causes the induction of the superoxide production originated from the activation of NADPH oxidase and uncoupled NO synthesis 21 .…”
Section: Introductionmentioning
confidence: 99%